O texto publicitário em sala de aula: modos de produção de sentido na formação do sujeito leitor - Casagrande, Jucirlei Pereira (2012)
This paper aims to propose a reflection about the production process of reading the text in advertising textbook Portuguese Languages William Robert Cherry and Thereza strand Magellan, the first year of high school and analyze the functionality of these texts in the formation of subject-reader, since reading the advertising copy used to enlarge the repertoire of the learner beyond the purely verbal text, greatly expanding the discursive competence. Furthermore, advertising is part of the everyday student, is a text of great social movement and therefore, according to the guidelines of Curriculum Proposal of Santa Catarina and the National Curriculum, should be part of the Portuguese language classes to a production job read. The research is guided by the concepts of Discourse Analysis of French orientation, as Pecheux and Orlandi, who brings the historical framework as the constitution of the subject, ideology as a determinant in the production of meaning and reading as the critical moment in the relationship between author / text / reader. And, within this perspective of reading as a discursive practice, in which the reader is challenged by the subject-position that affects (dis) builds the text read and gives directions that are not always as expected by the author. The research investigates the posture of the textbook on the recommendations of working with textual diversity and increase the capacity of the student reader through new readings, besides those common to textbooks, namely the advertising text.